Influence of food (ciliate and phytoplankton) on the trophic transfer of inorganic and methyl-mercury in the Pacific cupped oyster Crassostrea gigas. (February 2020) - Metian, Marc; Pouil, Simon; Dupuy, Christine; Teyssié, Jean-Louis; Warnau, Michel; Bustamante, Paco
Abstract: Diet is an important route of mercury (Hg) uptake in marine organisms. Trophic transfer of Hg throughout the food webs may be influenced by various factors, including diet and Hg speciation. Bivalves such as oysters are widely used as bioindicators of trace element pollution such as Hg. Nevertheless, our current knowledge regarding their ability to accumulate Hg from their diet is mainly based on experiments performed using phytoplankton. In their natural environment, oysters feed on a variety of food items including ciliates, detritus, in addition to phytoplankton. The present study aimed at examining the influence of diet composition on the trophic transfer of inorganic Hg (iHg) and methylmercury (MeHg) in the Pacific cupped oyster Crassostrea gigas . The pulse-chase feeding method was used with two radiolabeled food items: a heterotrophic protist ( Uronema marin um ) and a phytoplanktonic diatom ( Thalassiosira pseudonana ). Depuration of dietary Hg in the oysters was followed for 50 d. Kinetic parameters including assimilation efficiency (AE) and efflux rate constant (ke ) were calculated. Our results showed that oysters fed on ciliates assimilated 96 ± 1% and 31 ± 2% of the ingested MeHg and iHg, respectively whereas these elements were similarly assimilated in the oysters fed on phytoplankton (78 ± 3% and 86 ± 4% for MeHg and iHg, respectively). Mercury assimilation in oyster is thus diet dependent (significant differences in AE, p < 0.05), metal species-dependent and likely resulting from variations in Hg bioavailability in the two food items tested and a gut passage time-dependent of the ingested matrix. Graphical abstract: Image 1 Highlights: Ciliates are for first time considered as feed to assess the trophic transfer of elements in bivalves. Assimilation of Hg in C. gigas differs in response to the different diets tested. Highest assimilation of Hg in C. gigas is observed when it is fed with ciliates containing MeHg. Assimilation of Hg species in C. gigas for a given food.